Dampak Broken Home terhadap Siswa SMK N 1 Kudus Tahun 2021/2022 - M. Alfin Nur Kholil; Heri Saptadi Ismanto; Agus Setiawan (Departement of Mathematics Education, 2023)
The purpose of this research is to find out the impact of the Broken Home family on student learning activities at SMK N 1 KUDUS. This research was conducted using qualitative research methods. The data collection technique used by researchers in this study was on four students at SMKN 1 Kudus who experienced a Broken Home family through observation, interviews and documentation. Based on the results of the research findings and the results of the analysis presented in the special coding table for the four informants, it is related to how the impact of a broken home has on the learning activities of students at SMK N Kudus. From the four research informants, it shows that students' learning activities are classified as low. In addition, the findings in this study also resulted in that the aspects of asking questions and expressing opinions were most owned by students who experienced broken home problems. The lowest aspect that is most rarely raised in learning activities is giving ideas or ideas, proposing different thoughts and working independently. Based on the conclusions from research on the impact of a broken home on student learning activities at SMKN 1 Kudus, it shows that student learning activity is quite low. Students who experience these problems are unable to control their emotions while at school. Basically every student has the same ability in learning, but there are things that make them different, one of which is a broken home family. If there are problems in the family and the parents are not with the child, the child will lack attention and support in learning, this will make the child tend to think about family problems and not focus during the learning process.